Développement durable en zones côtières : comment territorialiser l’intérêt général environnemental ?Un cadre d’analyse - Jean-Eudes Beuret; Anne Cadoret; Hélène Rey-Valette (Développement Durable et Territoires)
Projects of protected areas or infrastructures justified by the fight against climate change often create, within territories, oppositions between global and local environmental stakes. The issue is to build a territory-based general interest and a sustainable territorial development. Coastal areas are local-global interface spaces, which offer favorable framework to analyze these processes. Drawing from cases studies and collective thinking, we identify five fundamental components in the building of territory-based general interest: the prioritization of actors, scales and stakes; adjustments of project; transactions between actors; spaces exit and the construction of new organized proximities.